Drug Planning At Andi Makkasau Hospital In Parepare City - Ode, Wahyuni L; Wulandari, Nur Astuti; Ramadhani, Nurul (Universitas STRADA Indonesia, 2021)
Background: Medicine is a very important element for efforts to improve health, prevention, diagnosis, treatment, and recovery which must be endeavored to always be available when needed. One of the important resources is the supply of medicines, especially in hospitals. The provision of drugs should be in accordance with the amount of treatment needed. If the supply of drugs is not smooth, it will hamper health services. Purpose: to obtain information on drug planning at the Andi Makassau Hospital, Parepare City. Method: the research uses a phenomenological descriptive approach. Data collection was carried out using an interview method conducted at the Andi Makkasau Hospital, Parepare City in August 2019. Results: Information on drug planning at Andi Makkasau Hospital was obtained from interviews with the head of the pharmacy installation, the person in charge of planning and planning staff. Conclusion: Drug planning at the Hospital Pharmacy installation uses the epidemiological method and the consumption method, those involved in the planning method are the pharmacy warehouse, the planning team, the supply division and the head of the installation. Guidelines for drug planning based on DOEN, Hospital Formulary, hospital therapy standards, available budget, remaining inventory, and past period usage